Revisiting B cell tolerance and autoantibodies in seropositive and seronegative autoimmune rheumatic disease (AIRD). (15th November 2020) - Pouw, J N; Leijten, E F A; van Laar, J M; Boes, M
Summary: Autoimmune rheumatic diseases (AIRD) are categorized seropositive or seronegative, dependent upon the presence or absence of specific autoreactive antibodies, including rheumatoid factor and anti-citrullinated protein antibodies. Autoantibody-based diagnostics have proved helpful in patient care, not only for diagnosis but also for monitoring of disease activity and prediction of therapy responsiveness. Recent work demonstrates that AIRD patients develop autoantibodies beyond those contained in the original categorization. In this study we discuss key mechanisms that underlie autoantibody development in AIRD: defects in early B cell development, genetic variants involved in regulating B cell and T cell tolerance, environmental triggers and antigen modification. We describe how autoantibodies can directly contribute to AIRD pathogenesis through innate and adaptive immune mechanisms, eventually culminating in systemic inflammation and localized tissue damage. We conclude by discussing recent insights that suggest distinct AIRD have incorrectly been denominated seronegative. Graphical Abstract: